(Re)thinking Repairs in the Longue Durée - Bernasconi, Gianenrico; Guillaume Carnino; Liliane Hilaire-Pérez; Olivier Raveux (My University, 2024)
The history of repairs underscores the complexity of time through the practices of reusing and adapting objects. While this research field primarily focuses on the contemporary period, its close ties to present-day life risk obscuring the historical depth of these practices and the stakes they hold in various societies. How can we incorporate a truly historical perspective into our understanding of repairs? This article, a product of collective reflection, aims to broaden the analysis of repairs by embracing the concept of longue durée , a term coined by Fernand Braudel to describe an extensive span of historical time. Rather than striving to construct a grand narrative, this article addresses the challenge of acknowledging the diverse contexts and the discrepancies in how individuals interact with the lifespan of materials, artifacts, and their functionalities.